Efektivitas Model Pull Out dengan Media Papan Flanel terhadap Hasil Belajar PAI Siswa ABK Kelas VIII di SMP N 9 Salatiga - Afiyah Assalam; Guntur Cahyono (Lembaga Yasin AlSys, 2025)
The limited number of studies on the use of the pull-out model with flannel board media in Islamic Religious Education (PAI) instruction for students with special needs (ABK) serves as the background of this research, given its strategic potential in optimizing learning outcomes and realizing inclusive education goals. This study aims to determine the effectiveness of the pull-out model assisted by flannel board media on the PAI learning outcomes of ABK students in Grade VIII at SMP Negeri 9 Salatiga. A quantitative approach with a quasi-experimental design was employed, involving four students each in the control and experimental groups, selected through purposive sampling. The primary instrument was a learning outcome test, with data analyzed using the independent sample t-test and N-Gain analysis. The results show a significance value of 0.032 (< 0.05) and an N-Gain score of 72% in the experimental class compared to 37% in the control class, indicating a higher improvement in learning outcomes among students who received the intervention. These findings align with Dale’s Cone of Experience theory, which posits that active involvement through visual and tactile experiences enhances students’ comprehension of learning material. The main conclusion is that the implementation of the pull-out model using flannel board media is effective in improving PAI learning outcomes for students with special needs. The study's implications include strengthening the literature on adaptive learning strategies for ABK and offering practical recommendations for teachers and schools to adopt contextual learning approaches tailored to students' characteristics. This research also opens avenues for further studies on the development of other models and media in inclusive classrooms.